2011
DOI: 10.1111/j.1600-0501.2010.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

One abutment at one time: non-removal of an immediate abutment and its effect on bone healing around subcrestal tapered implants

Abstract: The non-removal of an abutment placed at the time of surgery results in a statistically significant reduction of the horizontal bone remodeling around the immediately restored, subcrestally placed, tapered implant in cases of partial posterior mandibular edentulism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
1
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 16 publications
10
118
1
9
Order By: Relevance
“…Two studies reported no difference in peri-implant bone loss at 3 months (1,6), whereas two studies showed significant differences favoring the use of definitive abutments at 12 months (3,4). The measurement of horizontal and vertical marginal bone changes is considered important because inflammatory cell infiltrate at the implant-abutment junction affect bone remodeling in both directions (2,19,20). This meta-analysis showed that higher follow-up period was associated with less bone loss for one abutment at one time.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Two studies reported no difference in peri-implant bone loss at 3 months (1,6), whereas two studies showed significant differences favoring the use of definitive abutments at 12 months (3,4). The measurement of horizontal and vertical marginal bone changes is considered important because inflammatory cell infiltrate at the implant-abutment junction affect bone remodeling in both directions (2,19,20). This meta-analysis showed that higher follow-up period was associated with less bone loss for one abutment at one time.…”
Section: Discussionmentioning
confidence: 85%
“…Within 3 to 6 months after loading, results varied among studies (3,4,6). At 12 months, differences in peri-implant bone levels were observed between groups in two studies (2)(3)(4). Compared with provisional implants, definitive abutments resulted in less bone loss.…”
Section: Radiographic Evaluation and Measurement Of Periimplant Vertimentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this approach has been revised: implants placed closer to the palatal wall are used and reduced diameter implants have been advocated, 3 with the intention of reducing the predicted bone loss on the buccal side as much as possible. In a recently published paper, 6 the authors studied the effects of abutment removal on bone healing after the subcrestal placement of immediately restored tapered implants placed in healed sites and observed a statistically significant reduction of horizontal bone dimensional change. Originally, the increase of the sinking depth of the collar of standard two-piece butt-joint connection implants was supposed to compensate for the loss of vertical bone height, 4 but some authors demonstrated that this implant design results in an increased bone loss if placed beneath the bone crest.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, although being a 2-piece implant, the rough SLActive implant surface and its insertion position (at bone crest level) may also have contributed to bone level crest stability outcomes that were found. Degidi et al (2010) observed from an human study that a small but significant horizontal bone loss (non vertical) was evidenced in the hard tissue portion over the Marginal bone and soft tissue behavior following platform switching abutment connection/ disconnection -a dog model study 169 subcrestal implant platform in a period of time between the 6-months and 1-year follow-up when the abutment was removed to impression taken compared with the "one abutment at one time" concept when the abutment was applied immediately at time of implant placement. This difference seemed to be maintained over the 3-year period of the study.…”
Section: Aggregatibacter Actinomycetemcomitans Tannerella Forsythensmentioning
confidence: 99%